PENGARUH KEPUASAN SISWA TERHADAP LAYANAN PROGRAM MAKAN BERGIZI GRATIS PADA MOTIVASI BELAJAR SISWA SMP SWASTA TELADAN PEMATANGSIANTAR - Ayu Tresya Gultom; Anggun Tiur Ida Sinaga; Benjamin Albert Simamora (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine and analyze the effect of student satisfaction with the Free Nutritious Meal Program (MBG) service on students’ learning motivation at SMP Swasta Teladan Pematangsiantar. The background of this study is based on the low learning motivation of some students and the differences in the level of student satisfaction with the implementation of the Free Nutritious Meal Program at school. Student satisfaction with the program services is assumed to be one of the external factors influencing students’ learning motivation. This study employed a quantitative approach using a survey method. The population consisted of all students of SMP Swasta Teladan Pematangsiantar in the 2025/2026 academic year, totaling 194 students. The sample of 131 students was determined using the Proportionate Stratified Random Sampling technique with the Slovin formula. Data collection techniques included observation and questionnaires using a Likert scale. The data analysis techniques used were validity test, reliability test, descriptive statistics, normality test, heteroscedasticity test, simple linear regression analysis, t-test, and coefficient of determination (R²). The results of the study indicate that there is a positive and significant effect of student satisfaction with the Free Nutritious Meal Program (MBG) service on students’ learning motivation at SMP Swasta Teladan Pematangsiantar. The higher the level of student satisfaction with the MBG service, the higher the students’ learning motivation. The MBG program, through good service quality such as punctual food distribution, food cleanliness, menu variety, and service convenience, is able to improve students’ enthusiasm and motivation in participating in learning activities.